National Trends in Oral Anticoagulant Use in the United States, 2007 to 2011 - Kirley, Kate; Qato, Dima M.; Kornfield, Rachel; Stafford, Randall S.; Alexander, G. Caleb (Circulation Cardiovascular quality and outcomes, 2012)
Little is known regarding the adoption of direct thrombin inhibitors in clinical practice. We examine trends in oral anticoagulation for the prevention of thromboembolism in the United States. We used the IMS Health National Disease and Therapeutic Index, a nationally representative audit of office-based providers, to quantify patterns of oral anticoagulant use among all subjects and stratified by clinical indication. We quantified oral anticoagulant expenditures using the IMS Health National Prescription Audit. Between 2007 and 2011, warfarin treatment visits declined from ≈2.1 million (M) quarterly visits to ≈1.6M visits. Dabigatran use increased from 0.062M quarterly visits (2010Q4) to 0.363M visits (2011Q4), reflecting its increasing share of oral anticoagulant visits from 3.1% to 18.9%. In contrast to warfarin, the majority of dabigatran visits have been for atrial fibrillation, though this proportion decreased from 92% (2010Q4) to 63% (2011Q4), with concomitant increases in dabigatran's off-label use. Among atrial fibrillation visits, warfarin use decreased from 55.8% visits (2010Q4) to 44.4% (2011Q4), whereas dabigatran use increased from 4.0% to 16.9%. Of atrial fibrillation visits, the fraction not treated with any oral anticoagulants has remained unchanged at ≈40%. Expenditures related to dabigatran increased rapidly from $16M in 2010Q4 to $166M in 2011Q4, exceeding expenditures on warfarin ($144M) in 2011Q4. Dabigatran has been rapidly adopted into ambulatory practice in the United States, primarily for treatment of atrial fibrillation, but increasingly for off-label indications. We did not find evidence that it has increased overall atrial fibrillation treatment rates.